Prison same-sex sexualities in the context of politicized homophobia in Malawi. (February 2021) - Currier, Ashley
Prison same-sex sexualities have largely gone unnoticed in Malawi, an African nation associated with politicized homophobia. The term 'politicized homophobia' refers to political elites' public hostility toward same-sex sexualities, gender variance, and gender and sexual diversity activism. In a context typified by scrutiny of same-sex sexualities, it is surprising that certain same-sex sexual practices, specifically prison same-sex sexualities, escaped rebuke and attention in news media, which play an important role in circulating discourses of politicized homophobia in contemporary African nations. Using the case of prison sex in Malawi, this article asserts that politicized homophobia has verifiable limits because not all negative discourses about same-sex sexualities agglomerate into politicized homophobia. The essay draws on an analysis of 109 Malawian newspaper articles published between 1995 and 2016 that mention prison sex.